The Effect of Using Quizizz Learning Test Media on Thematic Learning Outcomes of Class II Students at MI Pembangunan UIN Jakarta - Cecep Maman Hermawan; Intan Aprillia; Rizky, Marsyah Qoriatul; M. Mu’thasim Billah; M. Fadhlurrahman; Okta Rosfiani (Enigma Institute, 2024)
Learning media is one of the factors that can influence student learning outcomes. One of the learning media that can be used to improve student learning outcomes is Quizizz. Quizizz is a game-based learning application that can be used to create quizzes, practice questions, or evaluate learning. This research aims to determine the effect of using the Quizizz learning test media on the thematic learning outcomes of class II students at MI Pembangunan UIN Jakarta. This research uses a quasi-experimental method with a pretest-posttest control group design. The sample for this research was 38 class II students at MI Pembangunan UIN Jakarta who were divided into two groups, namely the experimental group (20 students) and the control group (18 students). The experimental group used the Quizizz learning test media, while the control group used conventional learning media. The results of the research show that there is a significant influence between the use of the Quizizz learning test media and the thematic learning outcomes of class II students at MI Pembangunan UIN Jakarta. This is proven by the t-test results, which show that the calculated t-value (2.321) is greater than the t-table value (1.645) with a significance value of (0.028) < 0.05. Based on the results of this research, it can be concluded that the use of the Quizizz learning test media can improve the thematic learning outcomes of class II students at MI Pembangunan UIN Jakarta.